2011
DOI: 10.1163/092050610x488232
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Composite of Demineralized Bone Matrix Fragments and Polylactide Beads for Bone Tissue Engineering

Abstract: A composite that utilizes the osteoinductivity of demineralized bone matrix (DBM) and the attractive characteristics of polylactide (PL) may be useful as a tissue-engineered bone substitute. The objective of this study was to investigate the potential of a composite system consisting of DBM fragments and PL beads to support the attachment and proliferation of multipotent mouse marrow stromal cells and to provide a structure for the cells' differentiation into the osteoblast lineage. Furthermore, the overarchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…ASCs have been used together with acellular matrices from different sources. Allografts and xenografts have been derived mainly from bone tissue [55, 58, 60, 76, 77] but also from small intestine submucosa [57] or from adipose tissue [59].…”
Section: Scaffolds and Adipose Stem Cellsmentioning
confidence: 99%
“…ASCs have been used together with acellular matrices from different sources. Allografts and xenografts have been derived mainly from bone tissue [55, 58, 60, 76, 77] but also from small intestine submucosa [57] or from adipose tissue [59].…”
Section: Scaffolds and Adipose Stem Cellsmentioning
confidence: 99%
“…160,161 To take advantage of this property, decellularized tissues can be powdered and mixed with synthetic polymeric materials during scaffold formation to confer tissue-specific bioactivity to synthetic scaffolds. This hybrid approach employs a combination of the top-down (decellularized tissue) and bottom-up (incorporating a bioactive component into a synthetic scaffold) approaches for the modification of synthetic scaffolds.…”
Section: Hybrid Approaches For Bte Scaffold Modificationmentioning
confidence: 99%
“…Although DBM is weakened during the demineralization process, several reports have shown that the inclusion of synthetic polymers with DBM resulted in increased construct mechanical integrity. 56,69,118 Blends of natural and synthetic polymers have also been electrospun to create a bioactive scaffold with enhanced mechanical properties. GAG/collagen electrospun materials were used to facilitate dermal regeneration.…”
Section: Structural Propertiesmentioning
confidence: 99%